An Analysis of the resettlement program (Case Study: Dagon Myothit and Ayemyathaya Myothit) - Htoo, Thida (KDI School, 2000)
Urban development in Yangon (Capital of Myanmar) caused higher population density. Consequently, the government carried out a resettlement program by establishing new towns to relieve the problems, which arose due to the lower standard of living of urban residents and appearance of other socio-economics problems. This study examines the two main patterns of resettlement, namely urban resettlement and rural resettlement. Dagon Myothit, located in Yangon Division, was chosen to be analyzed as urban resettlement and Ayemyathaya Myothit, situated in Oakpo Township in Bago Division, was chosen to be analyzed as rural resettlement. The case study was based on a survey of 100 of plots from two blocks in Ayemyathaya Myothit chosen by the random sampling method and also 209 of plots from two blocks in Dagon Myothit (East) chosen in the above method. The sample plots taken from 1996 modified ward peace and development council census data and used as a sample frame were chosen by random sampling method. The information received from the case study is analyzed by quantitative and qualitative approach. The main findings of this study are that housing conditions were better only if the government could loan the necessary cost to settlers for construction, those without loans for construction of housing were in a worse condition. Regarding the electricity condition, in Dagon Myothit was supplied more than Ayemyathaya Myothit. There was no difficulty for water availability as a result of depending on the source of private water supply in the two regions. But Ayemyathaya Myothit relied heavily on public water supply compared with Dagon Myothit. On the educational level, there were many graduates in Dagon Myothit but most of the people of Ayemyathaya Myothit were at the level of secondary education. Households in Dagon Myothit earned higher household income compared with those in Ayemyathaya Myothit, for most of those in Dagon Myothit were government servants and could more easily get job opportunities consistent with urban life as a result of being located near the main city. Among the households who were resettled to Ayemyathaya Myothit, only one half of them specialized in farming. Yet the remainder returned to their former home site, as the creation of land for cultivation supplied by government and private home industries could not give income incentives for them, and these job opportunities were not suitable for their habits and interests. Consequently, in implementing the urban resettlement program, it became beneficial to live in their own houses for the households in two regions, but in supporting basic needs, there were conditions supported by the government, as well as the condition of selfreliance. In creating employment opportunity consistent with their educational level, to earn sufficient income to cope with their living expenses, households in Ayemyathaya Myothit were lacking in specialization in farming. Because in urban areas the opportunity for casual job was enormous, their income could be earned more easily than farming. Among the households who were resettled into the two regions there were some households who did not settle down there, as well as households who returned to their former home sites or moved to other places. The enumerator assumes that later studies will be more complete if enumerators can trace both these households. Their opinions will be able to be described in analyzing the achievement of resettlement program
Thesis(Master) -- KDI School: Master of Public Policy, 2000